RESEARCH ON COLLISION SIMULATION AND OPTIMIZATION OF CAB STRUCTURE OF A COMMERCIAL VEHICLE - LIN ChangBo; LI DongHai; DENG JuCai; XU EnYong; HE ShuiLong (Jixie qiangdu)
In order to comprehensively improve the commercial vehiele collision performance and protect the personal safety, at the time of standards change, a certain type of truck that passed GB 26512—2011 was taken as the research object, the frontal A-pillar pendulum impact test and top strength test added by GB 26512—2021 standard were taken as the object of investigation. The cab collision simulation model was established in Hypermesh, and the accuracy of the finite element model was verified through the real vehicle frontal collision test. In view of the intrusion in the top strength test, the structural sensitivity and foree transmission path were combined to optimize, and the corresponding structural optimization scheme was pгорosеd. The results show that the optimized cab structure has enough living space and meets the collision requirements of the new national standard.